Assessing Bioconcentration and Biotransformation of BDE-47 In Vitro: The Relevance of Bioavailable and Intracellular Concentrations - Paloma De Oro-Carretero; Jon Sanz-Landaluze (Journal of Xenobiotics, 2025)
The development of alternative methods that link cellular and predictive toxicity to high-level toxicity is a key focus of current research within the framework of the 3Rs in animal experimentation. In this context, this study aimed to evaluate the previously developed in vitro approach using the zebrafish liver cell line (ZFL) for assessing bioaccumulation and biotransformation of the compound BDE-47, which is more hydrophobic than phenanthrene, and is the compound used in the previous study. For this purpose, experimentally, the internal concentrations in the cells (Ccell) and the exposure medium of both BDE-47 and its main metabolites were quantified at different exposure times by GC-MS. Additionally, the free bioavailable concentration (Cfree) was determined with a solid-phase microextraction (SPME) experiment. With the aim of refine models, Ccell and Cfree were also estimated using a predictive chemical distribution model (MBM). Bioconcentration factors (BCFs) were determined by relating all these values, as well as by toxicokinetic fitting and by in vitro–in vivo extrapolation modelling (IVIVE). The results showed a high concordance with the values obtained in vivo. Moreover, the study highlighted the importance of experimentally determining Cfree and Ccell, as the predicted values can vary depending on the chemical, thereby influencing the BCF outcome. This variation occurs because models do not account for the absorption and biotransformation kinetics of the compounds. The data presented may contribute to refining predictive models.